2012
DOI: 10.2139/ssrn.2121212
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Location, and Internationalization: Empirical Evidence for Manufacturing SMEs

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 97 publications
0
3
0
3
Order By: Relevance
“…Each of these strategies may be supported by regulation of the localization or correction of spatial relationships of the enterprises with its business network (Lejpras, 2012).…”
Section: Localization and Competitive Strategiesmentioning
confidence: 99%
“…Each of these strategies may be supported by regulation of the localization or correction of spatial relationships of the enterprises with its business network (Lejpras, 2012).…”
Section: Localization and Competitive Strategiesmentioning
confidence: 99%
“…İnovasyonun doğrudan ihracat eğilimi üzerindeki olumlu etkisini gösteren bu sonuçlar Caldera (2010), Lejpras (2015), Ganatokis ve Love (2011), Becker ve Egger (2013) gibi literatür taraması kısmında bahsedilen çalışmalar ile de uyumludur.…”
Section: Tablo-1 Doğrudan İhracat Eğiliminin Belirleyicilerinde üRün Ve Süreç Yeniliğinin Rolüunclassified
“…, Merkez ve Doğu Avrupa ülkeleri ile Ortadoğu ve Kuzey Afrika ülkeleri için dolaylı ve doğrudan ihracat belirleyicilerini çalışmış ancak inovasyonun içselliğine değinmemiştir. ihracat yoğunluğu üzerindeki etkisine bakmış ve ürün ve süreç inovasyonlarının olumlu etkisini göstermiştir Lejpras (2015). de küçük ve orta ölçekli firmalar ile yaptığı çalışmasında inovasyonu temsil etmek üzere ürün inovasyonu ve patent başvurularını almış, inovasyonun firmaların ihracatçı olma eğilimini arttırdığını saptamıştır.…”
unclassified
See 1 more Smart Citation
“…To avoid the shortcoming of over-closeness, scholars suggested that cluster firms should reorganize their present knowledge networks via introducing nonlocal knowledge ties [6]. Most of the work in this area view relocation as a solution for firms facing cost pressure and innovative dilemma [13] or as a natural evolution process for clusters [14,15], especially for Chinese cluster firms, which have long been labeled as a proficient imitator. This is exemplified by the cross-border mobilization of Taiwan IT firms to mainland China since the 1990s [16] and the recent movement of manufacturing firms from Pearl River Delta to inland provinces in China [17].…”
Section: Introductionmentioning
confidence: 99%